Physico-Chemical Properties of Patchouli Oils (Pogostemon cablin) Separated by Fractional Distillation Method - Yuliani Aisyah; Sri Haryani Anwar (Syiah Kuala University, 2012)
Patchouli (Pogostemon cablin) is one species of the vegetation that produces essential oil known as patchouli oil. The quantity of patchouli alcohol contained in patchouli oil determines the oil quality. This study investigates fractional distillation of patchouli oils (Pogostemon cablin) to increase the level of patchouli alcohol in patchouli oils. The separation process is carried out by fractional distillation method applying four fractionation temperatures: 120°C, 125°C, 130°C, and 135°C. The compositions of each fraction were identified using Gas Chromatography – Mass Spectrometry (GC-MS). Patchouli oil A and B with initial patchouli alcohol content of 27.03% and 36.87% were successfully fractionated resulting four fractions of patchouli oils. The final levels of patchouli alcohol are increased to become 35.35% and 43.62%, respectively as well as the densities of the four fractions